Elucidation and modulation of active sites in holey graphene electrocatalysts for H2O2 production. Issue 1 (30th August 2022) - Koh, Ki Hwan; Bagherzadeh Mostaghimi, Amir Hassan; Chang, Qiaowan; Kim, Yu Joong; Siahrostami, Samira; Han, Tae Hee; Chen, Zheng
Abstract: Selective electrochemical oxygen reduction (ORR) toward a two‐electron (2e − ) pathway is an eco‐friendly alternative method for H2 O2 synthesis to replace the energy‐intensive anthraquinone oxidation process. Carbon‐based electrocatalysts (CBEs) show great potential for practical H2 O2 synthesis. However, their complex structures make it challenging to determine the nature of active sites and to precisely control them. Herein, we show that precise modulation of the chemistry and structures of holey graphene with edge sites enriched by oxygen‐containing functional groups can facilitate 2e − ORR. These combined functionalities could improve ORR performance under various pH conditions, for example, resulting in an average of 95% H2 O2 selectivity, 97% Faraday efficiency, high productivity of 2360 mol kgcat −1 h −1 in alkaline media. Density functional theory calculations on the oxygen functional groups at the edge sites revealed the most active site for 2e − ORR is a synergy between ether (COC) and carbonyl (CO) functional groups with nearly zero overpotential. Abstract : Functionalized hoely graphene possesses abundant inplane holes of which edges are decorated with ether/carbonyl groups. These functionalized hole edges are proved to be the most active site for 2e − ORR with nearly zero overpotential by density functional theory calculations. The theoretical activity is further confirmed by the experimental investigation showing 97% Faraday efficiency and high productivity of 2360 mol kgcat −1 h −1 in alkaline media.